Fabrication of High-Quality Er3+-Yb3+ Co-Doped Phosphate Glasses with Low Residual Hydroxyl Group Content - Yonglong Liu; Siyu Zhu; Jianan Huang; Xinyu Ye; Chunxiao Liu; Liaolin Zhang (Solids, 2025)
Rare earth-doped phosphate glasses have found widespread application in the field of solid-state and fiber laser technologies. Nevertheless, the fabrication of high-quality rare earth-doped phosphate glasses with minimal residual hydroxyl groups remains a significant challenge. To address this, a two-step melting process was utilized in this work to synthesize Er3+-Yb3+ co-doped phosphate glasses with low residual hydroxyl group content and improved optical quality. When re-melted under a N2 atmosphere at 900 °C for 12 to 16 h, the hydroxyl absorption coefficient (α-OH) decreased to ~1 cm−1. The structural and compositional characteristics of the glass remained essentially unchanged throughout the re-melting process. The weak broadband absorption in the visible range and the red-shift of the ultraviolet absorption edge were attributed to the reduction in residual hydroxyl group content rather than carbon contamination. The dehydroxylation mechanism was governed by the physical diffusion of hydroxyl groups within the glass matrix.